MiR30‐GALNT1/2 Axis‐Mediated Glycosylation Contributes to the Increased Secretion of Inactive Human Prohormone for Brain Natriuretic Peptide (proBNP) From Failing Hearts. Issue 2 (10th February 2017) - Nakagawa, Yasuaki; Nishikimi, Toshio; Kuwahara, Koichiro; Fujishima, Aoi; Oka, Shogo; Tsutamoto, Takayoshi; Kinoshita, Hideyuki; Nakao, Kazuhiro; Cho, Kosai; Inazumi, Hideaki; Okamoto, Hiroyuki; Nishida, Motohiro; et al.
Abstract : Background: Recent studies have shown that plasma levels of the biologically inactive prohormone for brain natriuretic peptide (proBNP) are increased in patients with heart failure. This can contribute to a reduction in the effectiveness of circulating BNP and exacerbate heart failure progression. The precise mechanisms governing the increase in proBNP remain unclear, however. Methods and Results: We used our recently developed, highly sensitive human proBNP assay system to investigate the mechanisms underlying the increase in plasma proBNP levels. We divided 53 consecutive patients hospitalized with heart failure into 2 groups based on their aortic plasma levels of immunoreactive BNP. Patients with higher levels exhibited more severe heart failure, a higher proportion of proBNP among the immunoreactive BNP forms secreted from failing hearts, and a weaker effect of BNP as estimated from the ratio of plasma cyclic guanosine monophosphate levels to log‐transformed plasma BNP levels. Glycosylation at threonines 48 and 71 of human proBNP contributed to the increased secretion of proBNP by attenuating its processing, and GalNAc‐transferase (GALNT) 1 and 2 mediated the glycosylation‐regulated increase in cardiac human proBNP secretion. Cardiac GALNT1 and 2 expression was suppressed by microRNA (miR)‐30, which is abundantly expressed in the myocardium of healthy hearts, but is suppressed in failing hearts. Conclusions: We have elucidated a novel miR‐30‐GALNT1/2 axis whose dysregulation increases the proportion of inactive proBNP secreted by the heart and impairs the compensatory actions of BNP during the progression of heart failure.